LEGAL ANALYSIS OF COMPENSATION TO DOCTORS AND HOSPITALS DUE TO DOCTORS' NEGLIGENCE (STUDY OF SUPREME COURT DECISION NUMBER 2921K/ Pdt/ 2018) - Mubarak, Rais Husni; T. Riza Zarzani N (International Journal of Synergy in Law, Criminal, and Justice, 2024)
This study evaluates the Supreme Court's decision Number 2921K/Pdt/2018 relating to medical malpractice cases and the legal responsibilities faced by doctors and hospitals in Indonesia. Using doctrinal analysis methods, this study focuses on regulations, jurisprudence, and the concept of vicarious liability in the context of unlawful acts. The focus of the analysis lies on the interpretation of the roles and responsibilities of doctors who fail to provide the expected standard of care and the hospital's responsibilities in internal supervision and management of health resources. The results of this study indicate a gap between the expected standard of care and the reality of practice in the field, often resulting in significant harm to patients. The recommendations provided emphasize the need to improve oversight mechanisms and implement policies that ensure strict supervision of medical practices in hospitals. This study hopes to encourage the use of alternative dispute resolution outside the courts for similar cases in the future, as mandated by Law Number 17 of 2023 concerning Health, which supports a more conciliatory and preventive approach in managing medical errors.